Digital Evidence in Pakistan: A Doctrinal Assessment of Admissibility and Reliability in Criminal Trials: https://doi.org/10.55966/assaj.2025.4.1.0107 - Sadia Nazir; Muhammad Asif; Asad U Allah Khan (`, 2025)
Digital evidence has been an essential element in criminal trials nowadays, although its admissibility and credibility in the Pakistani legal system is full of hindrances. This paper carries out a doctrinal evaluation of digital evidence in the criminal justice in Pakistan with analysis of legislative gaps, inconsistencies in the judiciary and shortcomings in the operation. The study looks at main laws such as the Qanun-e-Shahadat Order (1984) and the Prevention of Electronic Crimes Act (PECA), 2016 and finds tremendous ambiguity in authentication requirements and chain-of- custody practices. The comparative analysis presented against the jurisdiction of the U.S., UK and India through the study reveals the shortfall of international standards in the uptake of digital forensics in the Pakistani jurisdiction. The results show that there is a continued reluctance of the judiciary towards admitting digital evidence, worsened by the lack of forensic facilities, poorly trained investigators and cybersecurity weaknesses. The discussion highlights the failure of such shortcomings in reasonably enjoying the right to a fair trial as enshrined in Article 10A of the Constitution of Pakistan, especially by defendants who might not have the means to contest technical evidence. The researchers end the research with recommendations that can be carried out based on the findings, such as legislative changes in admissibility over the rules, specialized training of judges and investigators and the creation of accredited forensic labs. In dealing with these systemic deficits, Pakistan will be able to place the evidentiary standards in line with the best practices in the world, thus making digital evidence a powerful instrument of justice instead of a legal uncertainty. Keywords: Digital Evidence, Admissibility, Reliability, Criminal Trials, Pakistan, Qanun-e-Shahadat, PECA 2016, Digital Forensics, Judicial Training, Fair Trial Rights.